THE INFLUENCE OF COUNTRY OF ORIGIN AND CELEBRITY ENDORSEMENT ON PRODUCT PURCHASE DECISIONS VIVO SMARTPHONE: (Case Study on Mobile Global Customers of Lhoksumawe City) - Saremi, Hamid; Oktivani, Mutual; J, Jannatunnaim; Marbawi, Marbawi (RADJA PUBLIKA, 2021)
The results of this study show. (1) It can be seen that the adjusted R square value is 0.712 or 71.2%. This shows that the Country Of Origin Variable (X1), Celebrity Endorsement Variable (X2), can explain the Purchase Decision Variable (Y) of 28.8%, the remaining % (100% - 71.2%) is explained by other variables outside the research model. (2) The results of the t-test (partial) can be seen that the obtained tcount (11,076) > ttable (2,010), as well as the significance value of 0,000 <0.05, it can be concluded that the hypothesis first accepted, it means The Country Of Origin (X1) variable has a positive and significant effect on the Purchase Decision Variable (Y). (3) The results of the t-test (partial) can be seen that the value of tcount (0.634) < t table (2.010), and the significance value is 0.529 > 0.05, it can be concluded that the second hypothesis is rejected, meaning that Variable Celebrity Endorsement (X2) has no significant effect on the Purchase Decision Variable (Y). (4) The results of the simultaneous test (F) can be seen that the value of Fcount (61,617) > Ftable (3,18), and a significance value of 0,000<0.05, it can be concluded that the third hypothesis is accepted, meaning that Country Of Origin Variable (X1), Celebrity Endorsement Variable (X2), have a significant effect simultaneously (simultaneously) on Purchase Decision Variable (Y).